Effects of CGRP receptor antagonism in nitroglycerin-induced hyperalgesia. (July 2014) - Greco, R; Mangione, AS; Siani, F; Blandini, F; Vairetti, M; Nappi, G; Sandrini, G; Buzzi, MG; Tassorelli, C
Background: The release of calcitonin gene-related peptide (CGRP) from trigeminal nerves plays a central role in the pathophysiology of migraine and clinical evidence shows an antimigraine effect for CGRP receptor antagonists. Systemic administration of nitroglycerin (NTG), a nitrovasodilator, consistently provokes spontaneous-like migraine attacks in migraine sufferers; in the rat, systemic NTG induces a condition of hyperalgesia, probably through the activation of cerebral/spinal structures involved in nociceptive transmission. Aim: The aim of this article is to test the analgesic effect of the CGRP receptor antagonist MK-8825 in two animal models of pain that may be relevant for migraine: the tail flick test and the formalin test performed during NTG-induced hyperalgesia. Results: MK-8825 showed analgesic activity when administered alone at both the tail flick test and the formalin test. Furthermore, the CGRP antagonist proved effective in counteracting NTG-induced hyperalgesia in both tests. MK-8825 indeed reduced the nociceptive behavior when administered either simultaneously or prior to (30–60 minutes before) NTG. Conclusion: These data suggest that MK-8825 may represent a potential therapeutic tool for the treatment of migraine.